Communal Relationships: African-Americans’ Survival of Power is Deep-rooted in Zora Neale Hurston’s Jonah Gourd Vine - Kumar, Vasantha; Kumar, G. Rajesh (JETLEE: Journal of English Language Teaching, Linguistics, and Literature, 2022)
Zora Neale Hurston embodies all the logical inconsistencies, all the pinnacles and valleys of the writer’s life. She made her life, a memorial, and her spirits stay striking, flammable, stimulating and rousing, constantly modifying the world. Zora Neale Hurston has driven the route in drawing in the meanings of character and encounters inside connections. Her novel “Johah’s Gourd Vine” is scholarly substance is occupied with clarifying connections that can help rediscover the meaning of human relationships. Hurston like numerous other dark fiction journalists stress the dark preacher’s use of their way of life and history to make the African-American’s understands a world that is significant to them. This paper reveals the convention of dark self-assurance incorporates a sort of interior, regional dark patriotism and envelops free African-American populations.